São Tomé and Príncipe: 12 oil ministers since 1999, but not a single drop of oil yet - Seibert, Gerhard (2014)
In 1999, Luís dos Prazeres “Kapala”, a Nigerian-trained airline pilot and, since its inauguration in 2004, the executive director of São Tomé and Príncipe’s National Oil Agency (ANP), became the country’s first minister of natural resources. Since then, the small country has had another eleven ministers in charge of the oil portfolio.